2015
DOI: 10.1016/j.eucr.2015.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Renal Tuberculosis in a Partial Nephrectomy Specimen Done for Renal Tumor

Abstract: The association of renal cancer and renal tuberculosis is uncommon. While the incidental discovery of renal cell carcinoma in a tuberculous kidney is a classical finding, the discovery of tuberculous lesions after nephrectomy for cancer is exceptional. We report the case of a female patient aged 60 who had a partial nephrectomy for a 5 cm exophytic kidney tumor. Pathological examination concluded that renal clear cell carcinoma associated with follicular caseo tuberculosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…4,15 One case of renal tuberculosis was seen in this study similar to that by Basnet et al 4 No case of renal tuberculosis were present in studies done by Suryawanshi et al and Bajaj et al 8,10 Only few cases of accidental discovery of isolated renal tuberculosis have been reported in the literature. 20 Three cases showed nephrosclerosis along with chronic pyelonephritis two of which were seen in the age group of 60 to 69 years and the remaining one in the age group of 30 to 39. Truong et al studied the nonneoplastic renal diseases in nephrectomy specimens removed for tumor and found that nephrosclerosis was the most commonly associated lesion which probably represented aging changes or due to association with hypertension seen in these group of patients.…”
Section: Discussionmentioning
confidence: 93%
“…4,15 One case of renal tuberculosis was seen in this study similar to that by Basnet et al 4 No case of renal tuberculosis were present in studies done by Suryawanshi et al and Bajaj et al 8,10 Only few cases of accidental discovery of isolated renal tuberculosis have been reported in the literature. 20 Three cases showed nephrosclerosis along with chronic pyelonephritis two of which were seen in the age group of 60 to 69 years and the remaining one in the age group of 30 to 39. Truong et al studied the nonneoplastic renal diseases in nephrectomy specimens removed for tumor and found that nephrosclerosis was the most commonly associated lesion which probably represented aging changes or due to association with hypertension seen in these group of patients.…”
Section: Discussionmentioning
confidence: 93%
“…Most of the reported cases in the literature about pseudo tumor presentation of UGTB indicate that most of the cases presented with unilateral mass mimicking RCC and the diagnosis are always made after radical nephrectomy [ [5] , [6] , [7] ].…”
Section: Discussionmentioning
confidence: 99%
“…9,12,17,23,27 A rare case of association of renal TB with renal tumour was identified. 38 Few case reports of renal TB in paediatric patients were identified, including that of a 9-month-old. 9,18,23 Complications of renal TB include formation of sinuses and fistulae, psoas abscess, stricture formation in the renal collecting system, renal failure as well as arterial hypertension.…”
Section: Discussionmentioning
confidence: 99%